2023
DOI: 10.1007/jhep03(2023)182
|View full text |Cite
|
Sign up to set email alerts
|

Combined constraints on dark photons and discovery prospects at the LHC and the Forward Physics Facility

Abstract: Hidden sectors are ubiquitous in supergravity theories, in strings and in branes. Well motivated models such as the Stueckelberg hidden sector model could provide a candidate for dark matter. In such models, the hidden sector communicates with the visible sector via the exchange of a dark photon (dark Z′) while dark matter is constituted of Dirac fermions in the hidden sector. Using data from collider searches and precision measurements of SM processes as well as the most recent limits from dark matter direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 127 publications
(141 reference statements)
0
3
0
Order By: Relevance
“…The Boltzmann equations governing the evolution of the visible and hidden sectors are coupled and involve the evolution equation for ξ(T). Such an equation was derived in [39][40][41] and applied in a variety of settings in [42], consistent with all experimental constraints on hidden-sector matter from terrestrial and astrophysical data [43]. It is found that hidden sectors can affect observable phenomena in the visible sector, such as the density of thermal relics.…”
Section: Hidden Sectors Intertwine Particle Physics and Cosmologymentioning
confidence: 57%
“…The Boltzmann equations governing the evolution of the visible and hidden sectors are coupled and involve the evolution equation for ξ(T). Such an equation was derived in [39][40][41] and applied in a variety of settings in [42], consistent with all experimental constraints on hidden-sector matter from terrestrial and astrophysical data [43]. It is found that hidden sectors can affect observable phenomena in the visible sector, such as the density of thermal relics.…”
Section: Hidden Sectors Intertwine Particle Physics and Cosmologymentioning
confidence: 57%
“…Here we discuss experimental limits on dark matter that arises in the Stueckelberg extension of SM discussed in previous chapters and specifically on the dark fermion. The analysis presented in this chapter is based on the work of Ref [86].…”
Section: Combined Constraints On Dark Photons and Discovery Prospectsmentioning
confidence: 99%
“…In this Chapter, we focus on FASER experiment which is able to detect a long-lived dark photon. The analysis presented in this chapter is based on the work of Ref [86].…”
Section: Summary Of the Dark Photon Constraints And Potential Discoverymentioning
confidence: 99%